Greenhouse gas emissions, dry matter intake and feed efficiency of young Holstein bulls - Simone Callegaro; Giovanni Niero; Mauro Penasa; Raffaella Finocchiaro; Guido Invernizzi; Martino Cassandro (Italian Journal of Animal Science, 2022)
Livestock farming is directly responsible for greenhouse gas (GHG) emissions, mainly due to enteric fermentation. Feed efficiency in livestock species is generally evaluated through feed conversion ratio (FCR) and residual feed intake (RFI), which are associated to GHG emissions. The aim of this study was to characterise FCR and RFI in relation to body traits, feed intake, feeding behaviour and GHG emissions of Holstein bulls. Data were collected between May 2018 and July 2020 on 111 animals. Pearson correlations between studied traits were estimated on the residuals obtained from a linear mixed model which included the fixed effect of the linear covariate of age of bull on the dependent variable and the random effect of the bull. To assess the effect of RFI and FCR the same linear mixed model was implemented firstly by including the fixed effect of RFI (2 classes) and secondly the fixed effect of FCR (2 classes). Correlations between dry matter intake (DMI) and GHG ranged from 0.25 (CH4) to 0.36 (CO2). The strongest relationship was estimated between feed efficiency traits and DMI (0.86). RFI and FCR showed weak to moderate correlations with GHG (0.12–0.31). Animals belonging to the low classes of RFI and FCR had lower DMI and showed significant reduction of GHG emissions. Results of the present study highlighted significant differences in terms of feed efficiency and GHG emissions among tested animals; further research is needed on their progeny to investigate the genetic background of the same efficiency and emission-related traits. Highlights Feed efficiency and emission of greenhouse gases vary among Holstein bulls. Dry matter intake and feed efficiency traits were strongly positively associated. Animals endowed with greater feed efficiency had lower emissions and feed intake. Results of the present study will be useful to select animals for feed efficiency.